Leveraging the competitiveness of Eritrean agriculture: A case study. - Ravinder, Rena (IJRCM, 2010)
Agriculture is the backbone of Eritrean economy. It provides employment to over 70 percent of the working population in the country. In good years the country produces only about 60 per cent of its total food needs and in poor years, it produces no more than 25 per cent. Annual crop production mainly depends on rainfall that is variable and unevenly distributed from year to year. Agriculturalists, economists and experts from different fields of studies have raised alarm on food crisis. This paper delves the Eritrean agricultural production, land and people. It throws a light on the Elabered Estate,a reputed agricultural estate since the Italian period. It examines the strategies and methods used by the Estate to increase agricultural yields. It discusses varieties of grains with greater resistance to disease and pests, together with the use of improved farm management techniques and chemical inputs, such as improved pesticides and fertilizers. The paper highlights the success story of the Estate being an important player or a model in Eritrean agriculture sector. The paper deals with the concerted efforts made by the Estate to go with the Global Competition. It also highlights some of the challenges of Eritrean agriculture sector and provides implications.
Keywords: Agriculture - Eritrea; Eritrea - Agriculture